Clinical effect of a positive surgical margin after hepatectomy on survival of patients with intrahepatic cholangiocarcinoma - Yeh CN; Hsieh FJ; Chiang KC; Chen JS; Yeh TS; Jan YY; Chen MF (Dove Medical Press, 2014)
Chun-Nan Yeh,1 Feng-Jen Hsieh,1 Kun-Chun Chiang,1 Jen-Shi Chen,2 Ta-Sen Yeh,1 Yi-Yin Jan,1 Miin-Fu Chen1 1Department of General Surgery, 2Department of Medical Oncology, Chang Gung Memorial Hospital, Chang Gung University, Taoyuan, Taiwan Background: Several unfavorable prognostic factors have been proposed for peripheral cholangiocarcinoma (PCC) in patients undergoing hepatectomy, including gross type of tumor, vascular invasion, lymph node metastasis, a high carbohydrate antigen 19-9 level, and a positive resection margin. However, the clinical effect of a positive surgical margin on the survival of patients with PCC after hepatectomy still needs to be clarified due to conflicting results. Methods: A total of 224 PCC patients who underwent hepatic resection with curative intent between 1977 and 2007 were retrospectively reviewed. Eighty-nine patients had a positive resection margin, with 62 having a microscopically positive margin and 27 a grossly positive margin (R2). The clinicopathological features, outcomes, and recurrence pattern were compared with patients with curative hepatectomy. Results: PCC patients with hepatolithiasis, periductal infiltrative or periductal infiltrative mixed with mass-forming growth, higher T stage, and more advanced stage tended to have higher positive resection margin rates after hepatectomy. PCC patients who underwent curative hepatectomy had a significantly higher survival rate than did those with a positive surgical margin. When PCC patients underwent hepatectomy with a positive resection margin, the histological grade of the tumor, nodal positivity, and chemotherapy significantly affected overall survival. Locoregional recurrence was the most common pattern of recurrence. Conclusion: A positive resection margin had an unfavorable effect on overall survival in PCC patients undergoing hepatectomy. In these patients, the prognosis was determined by the biology of the tumor, including differentiation and nodal positivity, and chemotherapy increased overall survival. Keywords: surgical margin, hepatectomy, cholangiocarcinoma